WORK IN PROGRESS VICTORIAN STATIONMASTERS: ORIGINS AND OUTCOMES. (1st October 2012) - ,
Abstract : As not all members of the Family and Community Historical Research Society (FACHRS) have either the time or inclination to devote to one of its major research projects (Swing Riots, Allotments, Almshouses, School and Commmunity), the Society has introduced the mini-project, which, as the name suggests requires a more modest commitment. What follows is a report on the progress of the 'Stationmaster mini-project' by its co-ordinator, Dr Sue Smith.